Исследование процесса осаждения частиц взвешенных веществ в действующем макете усовершенствованного отстойника шахтных вод - Колесник, В.Е.; Куликова, Д.В. (Екологічна безпека та природокористування, 2012)
The physical modeling of process of deposition of the suspended materials in experimental model of sedimentation tank is conducted. The graphical layouts of deposition of the suspended particles subject to duration of process of settling at the different height of layer of the liquid and average speed settling of the suspended materials (hydraulic size of particles) are built. Distance on which the suspended particles of different hydraulic size will fall out on the bottom of experimental model of sedimentation tank at providing of the purification efficiency of mine waters is determined.